Konstruksi Keaktifan Belajar Siswa Kelas V SDN Ngegong Kota Madiun dalam Pembelajaran IPS Berbasis Flipped Classroom Pada Ruang Mediasi Quizizz - Sri Wahyuni; Nurhadji Nugraha; Yudi Hartono (Tamilis Synex: Multidimensional Collaboration, 2025)
Student learning engagement in elementary social studies instruction demonstrates considerable variation influenced by instructional approaches and the learning media employed. This condition indicates the need for a deeper understanding of the dynamics of student engagement when instruction is organized through flipped classroom learning within the mediation space of Quizizz. This study adopted a descriptive qualitative approach and was conducted with fifth-grade students at SDN Ngegong, Madiun City. Data were collected through classroom observations, interviews with teachers and students, and documentation of learning activities, and were analyzed using data reduction, data display, and conclusion drawing procedures. The findings indicate that student learning engagement in social studies emerged in diverse forms of participation reflecting cognitive, social, and responsive involvement throughout the learning process. The flipped classroom approach enabled classroom time to be utilized more intensively for interaction and discussion, while Quizizz functioned as a mediating space that facilitated immediate responses and active student participation.